THE USE OF ENGLISH SONG BY USING JOOX APPLICATION IN TEACHING ENGLISH PRONUNCIATION AT SMAN 7 MAKASSAR - Rahmayani, Rusni; Sujariati; Ardiana (FKIP Unismuh Makassar, 2023)
This study aims to determine the effectiveness of using English songs using the Joox application in learning pronunciation at SMAN 7 Makassar. The research method used in this study was pre-experimental with the data analysis process using a quantitative design. The population of this study were all students of class XI MIPA. And the sample in this study were students of class XI MIPA 3, totaling 36 students. The instrument used is a test of speaking skills in pronunciation terms through a pre-test and post-test. This research was conducted for 6 meetings. Based on the results of the study, it was found that the use of the Joox application was effective in improving students' pronunciation at SMAN 7 Makassar. The results of the pre-test pronunciation were 39.44 and the results of the post-test pronunciation were 62.08. The results showed an increase in pronunciation of 57.40%. In addition, the value of the t-test is higher than the value of the pronunciation t-table (14.963 > 1.690) which means that H0 is rejected and H1 is accepted. So it can be concluded from the results of this study that the use of songs through the Joox application in improving students' pronunciation at SMAN 7 Makassar.